2021
DOI: 10.3390/pharmaceutics13020165
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antimicrobic, Antivirotic and Cytotoxic Potential of Alginate Beads Cross-Linked by Bivalent Ions for Vaginal Administration

Abstract: Antimicrobial agent abuse poses a serious threat for future pharmacotherapy, including vaginal administration. The solution can be found in simple polymeric systems with inherent antimicrobial properties without the need to incorporate drugs, for instance alginate beads cross-linked by bivalent ions. The main goal of the presented study was to provide improvement on the well-documented cytotoxicity of Cu2+ cross-linked alginate. Alginate beads were prepared by external ionotropic gelation by cross-linking with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 77 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…It is also observed that these beads are clearly folded and cracked. As reported, these cracks were detected in the case of alginate beads cross-linked with divalent cations such as copper and calcium [70], in agreement with our results. On the other hand, the Alg@Ce bead is morphologically different., Firstly, beads are not cracked (Fig.…”
Section: Morphological Analysissupporting
confidence: 93%
“…It is also observed that these beads are clearly folded and cracked. As reported, these cracks were detected in the case of alginate beads cross-linked with divalent cations such as copper and calcium [70], in agreement with our results. On the other hand, the Alg@Ce bead is morphologically different., Firstly, beads are not cracked (Fig.…”
Section: Morphological Analysissupporting
confidence: 93%
“…This improvement is primarily attributed to the in-situ formation of copper-based MOFs within the copper-ion-crosslinked alginate beads, resulting in a three-dimensional structural arrangement. [39][40][41]…”
Section: Tga Analysismentioning
confidence: 99%
“…This observed efficacy is primarily attributed to copper ions interacting with the bacterial membranes, leading to the release of cellular contents and consequent cell death. [39,40] Copper ions can affect gram-positive and gram-negative bacteria differently owing to differences in their cell wall structures and membrane characteristics. Gram-positive bacteria feature a cell membrane consisting of a singular thick peptidoglycan layer.…”
Section: Evaluation Of the Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Alginate/chitosan NPs were tested with rifampicin encapsulation against MSSA and MRSA in pulmonary intracellular infections [ 243 ]. The results revealed that the alginate NPs have great potential as novel antimicrobial nanomaterials [ 242 , 244 ].…”
Section: Nanotechnology-based Approaches To Target Staphylo...mentioning
confidence: 99%